Knowledge, attitudes and practices on family planning of urban poor mothers with multiple children in a selected community in Quezon City - Juan, Marie Antonette A.; Manongdo, Dannah Mari Jelena N.; Quijano, Maria Lourdes M. (Quezon City U.P. College of Home Economics, 2013)
ABSTRACT The purpose of this research is to explore the knowledge, attitudes, and practices of urban poor mothers with multiple children on family planning. The study used purposive sampling to select the respondents residing in Phase 3 Lupang Pangako, Payatas B, Quezon City. The 30 respondents were interviewed with the use of a self-devised interview guide. All of the mothers have heard about family planning and perceive its importance to them. However, results show that only 90% of them utilize their acquired family planning knowledge to select the best fit family planning method for their lifestyle. 96.67% of the mothers approve of the use of the family planning methods mainly because they wanted to control the number of the children in the household and they believe it is a way to avoid poverty. Having the knowledge and adoption of family planning and its methods, 86.67% have used the family planning methods, mainly pills, to control the number of their children in the household. Still, all of the mothers have four or more children. The results of this study show that insufficient family planning knowledge may influence the family planning practices of the mothers. The researchers see that the data gathered may help in the improvement of the family planning programs that will benefit the residents in the selected area of study.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Family planning -- Philippines -- Quezon City; Urban poor -- Philippines -- Quezon City